COUNSELING ISLAMIC-BASED DIGITAL LITERACY TO OVERCOME OVERSHARING BEHAVIOR ON SOCIAL MEDIA - Hamzanwadi, Hamzanwadi; Zainul Mukminin, Emha (Universitas Islam Negeri Mataram, 2024)
The rapid advancement of information and communication technology, particularly social media, has significantly influenced societal interaction patterns. Among the negative outcomes of social media usage is oversharing behavior, characterized by excessive disclosure of personal information, which threatens privacy, mental health, and social relationships. This study examines the role of Islamic counseling integrated with digital literacy in addressing oversharing on social media. Digital literacy here involves understanding ethical information sharing, digital identity management, and the consequences of online actions. Islamic counseling, emphasizing moral and ethical values from Islamic teachings, aims to provide individuals with insights and practical strategies to regulate oversharing tendencies. A qualitative research approach was adopted, utilizing literature analysis and interviews to explore the perspectives of individuals engaging in such behavior. The findings suggest that Islamic counseling, supported by digital literacy education, is an effective approach to fostering responsible social media use. This integration enhances awareness of privacy, self-respect, and ethical online behavior, mitigating the adverse effects of oversharing and promoting a balanced and conscious engagement with digital platforms.